2006
DOI: 10.3354/meps322099
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the distribution of Pyrodinium bahamense var. bahamense in coastal waters of Florida

Abstract: Over the last half of the 20th century Pyrodinium bahamense var. bahamense has been observed in a variety of locations in the western North Atlantic. Recent evidence of the toxinproducing capacity of this variety of P. bahamense has heightened interest in its habitat requirements and preferences. The objective of this study was to examine the environmental factors that relate to the spatial and temporal patterns of the distribution and abundance of P. bahamense var. bahamense. Based on the results of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 40 publications
(62 reference statements)
4
82
0
1
Order By: Relevance
“…In the subtropical estuaries of Florida subject to large freshwater inflows, the eurythermal and euryhaline character of A. sanguinea make it a competitive species throughout the year, yielding bloom events inside and outside the more typical warm season peak period of phytoplankton biomass in many Florida ecosystems. In Florida, this pattern is in contrast to bloom events of another major HAB species in Florida estuaries, the toxic dinoflagellate Pyrodinium bahamense, which is typically restricted to temperatures in excess of 25°C, reflecting the tropical nature of the species (Phlips et al 2006). Akashiwo sanguinea is indeed an alga for all seasons.…”
Section: Discussionmentioning
confidence: 85%
“…In the subtropical estuaries of Florida subject to large freshwater inflows, the eurythermal and euryhaline character of A. sanguinea make it a competitive species throughout the year, yielding bloom events inside and outside the more typical warm season peak period of phytoplankton biomass in many Florida ecosystems. In Florida, this pattern is in contrast to bloom events of another major HAB species in Florida estuaries, the toxic dinoflagellate Pyrodinium bahamense, which is typically restricted to temperatures in excess of 25°C, reflecting the tropical nature of the species (Phlips et al 2006). Akashiwo sanguinea is indeed an alga for all seasons.…”
Section: Discussionmentioning
confidence: 85%
“…Laboratory studies on cells were isolated from Malaysia (Usup, 1995) showed that the temperature limits for growth are 22-34°C, with optimum growth at 28°C. Phlips et al (2006) reported that cells of P. bahamense var. bahamense appeared in the column of water when the water temperature reached 20°C and blooms of this species formed only when the temperature was 25°C or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Although blooms only occurred at 20 psu or higher, P. bahamense var. bahamense in Florida has a salinity range of 10-45 psu, (Phlips et al, 2006;Usup et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of P. bahamense var. bahamense in coastal waters of Florida suggests that the minimum temperature that limits its occurrence is 20°C (Phlips et al 2006). These temperature tolerances support po tential climate-related range expansion (Usup et al 2012).…”
Section: Temperaturementioning
confidence: 99%